PSYCHOLOGICAL AND PHYSIOLOGICAL BENEFITS OF GROUP EXERCISES FOR WOMEN - Buronova Sidiqa Tuxtayevna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the psychological and physiological benefits of group exercises for women. It examines how structured group training sessions improve mental well-being, motivation, social interaction, and adherence to physical activity, while simultaneously enhancing cardiovascular fitness, muscular strength, flexibility, and overall health. The study highlights the role of social support, collective motivation, and instructor guidance in optimizing the outcomes of group exercise programs. It also emphasizes the importance of tailoring exercises to individual abilities and needs to maximize both physical and psychological benefits.